2010
DOI: 10.1103/physrevlett.104.098101
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Transition of Protein-Hydration Water

Abstract: Thin layers of water on biomolecular and other nanostructured surfaces can be supercooled to temperatures not accessible with bulk water. Chen et al. [PNAS 103, 9012 (2006)] suggested that anomalies near 220 K observed by quasi-elastic neutron scattering can be explained by a hidden critical point of bulk water. Based on more sensitive measurements of water on perdeuterated phycocyanin, using the new neutron backscattering spectrometer SPHERES, and an improved data analysis, we present results that show no sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
206
1
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(227 citation statements)
references
References 34 publications
19
206
1
1
Order By: Relevance
“…The mean characteristic relaxation time τ is calculated from τ and β by τ = β −1 (β −1 )τ . In this study, β is fixed to 0.5, just as in the analysis of Doster et al [17] and a previous work by our group [12]. In addition, we have taken the elastic fraction p to be of the form p(Q) = p 0 A(Q), with p 0 constant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean characteristic relaxation time τ is calculated from τ and β by τ = β −1 (β −1 )τ . In this study, β is fixed to 0.5, just as in the analysis of Doster et al [17] and a previous work by our group [12]. In addition, we have taken the elastic fraction p to be of the form p(Q) = p 0 A(Q), with p 0 constant.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 in the sequence of E to guarantee that the Riemann sum of the normalized S th (Q,E) converges to 1; thus the numerical problem pointed out by Doster et al in Ref. [17] will not appear. Therefore, a direct comparison between the results in this study and in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This scenario was based on studies that advocated a second critical point of water (liquid-liquid critical point) in confined supercooled water [4]. However, a recent high resolution QENS experiment performed by Dosteret al [5] in fully deuterated C-phycocyanin protein, showed no evidence of such fragile-to-strong character in the dynamical transition at T D . As pointed out by these authors, their experimental findings are consistent with a glass transition of the hydration shell.…”
mentioning
confidence: 99%